2021
DOI: 10.31018/jans.v13i2.2579
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effect of polyethylene glycol and sorbitol on two banana varieties viz. Grand naine and Nalla bontha to study drought stress

Abstract: Water stress is one of the foremost categories of stress damaging plants’ overall growth and development. The aim of the present study was to explore and demonstrate stress-induced drought to calibrate changes in stress parameters of two banana plant varieties viz. Grand naine (G9)  and Nalla bontha were cultured in Murashige and Skoog medium (MS) media supplemented with stress inducers -Poly ethylene glycol (PEG)  and sorbitol. The different concentrations of inducers were used to induce drought stress in two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Al-Mayahi [51] found that adding PEG at 15% to MS media caused an increase in proline content of P. dactylifera L compared with control Re-culturing the micro-shoots of P. dactylifera L on MS media supplemented with Si at 3.6 mM combined with 15% PEG led to a decrease in proline content compared with those of control and culture media supplemented with PEG only. In addition, Singh et al [62] illustrated that adding PEG at 1% to 3% to the growth MS media caused an increase in proline content of two banana varieties viz. Grand naine and Nalla bontha compared with those of control and other treatments [62].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Al-Mayahi [51] found that adding PEG at 15% to MS media caused an increase in proline content of P. dactylifera L compared with control Re-culturing the micro-shoots of P. dactylifera L on MS media supplemented with Si at 3.6 mM combined with 15% PEG led to a decrease in proline content compared with those of control and culture media supplemented with PEG only. In addition, Singh et al [62] illustrated that adding PEG at 1% to 3% to the growth MS media caused an increase in proline content of two banana varieties viz. Grand naine and Nalla bontha compared with those of control and other treatments [62].…”
Section: Figurementioning
confidence: 99%
“…In addition, Singh et al [62] illustrated that adding PEG at 1% to 3% to the growth MS media caused an increase in proline content of two banana varieties viz. Grand naine and Nalla bontha compared with those of control and other treatments [62]. In Arabidopsis, higher levels of proline accumulation were linked to improved salt and drought resistance [63].…”
Section: Figurementioning
confidence: 99%
“…Orchids are also considered an important crop in the floriculture industry. This plant family is usually cultured due to its medicinal properties and uses in traditional food, as well as the generation of nutraceutical products, perfumes, and cosmetics (Hinsley et al, 2018;Kanlayavattanakul et al, 2018;Salazar-Mercado & Botello-Delgado, 2020;Singh et al, 2021). In recent years, many species of orchids have been threatened in their natural habitats because of the environmental pressure generated by humans (Juras et al, 2020;Fonseka, 2020;Puspitaningtyas & Handini, 2020).…”
Section: Introductionmentioning
confidence: 99%